PENGARUH COLLABORATIVE LEARNING TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN PERCOBAAN SISWA KELAS IX SMP NEGERI 24 PALEMBANG - Mulyati, Mulyati; Sari'ah, Sari'ah (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
The aim of this study was to determine the effect of collaborative learning models on students ability to write text of experimental report. The method used in this study is an experimental method through pretest and posttest. The population of this research was class IX students of SMP Negeri 24 Palembang, which totaled 147 students. The sample of this research was class IX students with 32 students. Data collection techniques used in this study were tests and questionnaires. Data analysis techniques used t-test. The results of this study can be concluded that the Collaborative Learning model take effect to the ability to write text of experimental report is significant, because it is proven t-score is greater than t-table at a significant level of 5% with db (free degrees) t-score (12,711) > t-table (1,696). So, the hypothesis put forward is proven true.